2020
DOI: 10.1016/j.measurement.2019.107240
|View full text |Cite
|
Sign up to set email alerts
|

An enhanced modulation signal bispectrum analysis for bearing fault detection based on non-Gaussian noise suppression

Abstract: Many methods have been developed for machinery fault diagnosis addressing only Gaussian noise reduction, the major weaknesses of these methods are their performance for non-Gaussian noise suppression. Modulation signal bispectrum (MSB) is a useful signal processing method with significant advantages over traditional spectral analysis as it has the unique properties of Gaussian noise elimination and demodulation. However, it is susceptible to non-Gaussian noise that normally occurs in the practical applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…The autoregressive (AR) model is a statistical method to deal with time series. It uses the values of the same variable in different periods to predict the present values and assumes that they are linear [ 13 ]. Therefore, it is called autoregressive.…”
Section: A Brief Description Of the Methods For Vibration Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The autoregressive (AR) model is a statistical method to deal with time series. It uses the values of the same variable in different periods to predict the present values and assumes that they are linear [ 13 ]. Therefore, it is called autoregressive.…”
Section: A Brief Description Of the Methods For Vibration Datamentioning
confidence: 99%
“…The Yule–Walker equation is an equation describing the relationship between the parameters of autoregressive sequence and its covariance function. The common equation set form is shown in Equation (2) [ 13 , 14 ]: …”
Section: A Brief Description Of the Methods For Vibration Datamentioning
confidence: 99%
“…where 𝑠(𝑡) indicates the periodic impulse component caused by rolling element bearing defect, and its model is formulated as [40]:…”
Section: Simulation Modelmentioning
confidence: 99%
“…(28) Among them, the BSD has outstanding fault identification performance. Previous studies revealed that the BSD method can eliminate Gaussian noise and extract feature parameters more effectively by combining it with autoregression (29) and singular value decomposition. (30) For these reasons, we propose a novel fault diagnosis method based on the BSD to extract the vibration as well as system-invariant characteristics of rolling-element bearings under variable operation conditions.…”
Section: Introductionmentioning
confidence: 99%